STUDY OF BER PERFORMANCE OF TURBO CODE USING DIFFERENT MODULATION SCHEME - K.Elaiyarani, K.Kannadasan, R.Sivarajan3, V.Nagarajan (International Journal of Research Science and Management, 2015)
The customary job for error-control coding was to build a channel tolerable by reducing the occurrence of error actions. The various errors arise in the communication systems are bit errors, message errors or invisiblenoiseerrors from channels. To avoid these errors, there are number of error control codes such as hamming code, cyclic code, convolution code and turbo codes are available. This paper presents the comparison of performance of bit error rate of convolution codes and turbo codes using BPSK and QAM Modulation in AWGN Channel